Acid-sensing Ion Channels: Implications for Intervertebral Disc Degeneration - Ran, Rui; Wu, Yi; Zhang, Hai-hong (Current Pharmaceutical Biotechnology, 2023)
Intervertebral disc degeneration (IDD) is the leading cause of lower back pain and seriously affects the quality of life of patients. The intervertebral disc (IVD) is an environment of hypoxia, ischemia, acidity, and hypertonicity. Matrix acidity potentially negatively affects gene expression, activity, proliferation, and apoptosis of IVD cells. Acid-sensing ion channels (ASICs) are a group of proton-gated ion channels that play important roles in physiological and pathological conditions. The distribution of ASICs in the nucleus pulposus (NP), annulus fibrosus, cartilage endplate, and nucleus pulposus mesenchymal stem cells (NP-MSCs), as well as the special functions of ASIC1a and ASIC3, show that ASICs play an important role in IDD. In this review, we comprehensively discuss the roles of ASICs in the development and basic pathology of IDD and their potential relevance as therapeutic targets. A deeper understanding of the roles of ASICs in these processes may provide novel therapeutic targets for IDD prevention and treatment.
Keywords: nucleus pulposus